Determination of leaf status of soybean varieties on shading : chlorophyll and chloroplast: Leaf status of soybean varieties on shading - LISA MAWARNI; TENGKU CHAIRUN NISA; JUSTIN A NAPITUPULU; KARYUDI KARYUDI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Mawarni L, Nisa TC, Napitupulu JA, Karyudi. 2019. Determination of leaf status of soybean varieties on shading. Biodiversitas 20: 615-620. The shading tolerant soybean varieties could be identified through the character growth such as leaf status. This study was aimed to obtain the shading tolerant of soybean variety based on their seed size and on the leaf status. Design of experiments was a split-plot design with three replications. The level of shading as the main plot with four levels of treatment was without shading, 30%, 50%, and 70% shading. Soybean varieties as the subplot had 4 genotypes namely Anjasmoro, Pangrango, Tanggamus, and Nanti wherein one variety comes with large seed; two come with medium seeds and the other one comes with small seed. The leaf status for determination was the greenness of leaves, the sum of chlorophyll a, chlorophyll b, total chlorophyll a and b, the forms of chloroplasts and leaf area. The soybean varieties with different seed sizes showed the differences only on the leaf area but not on leaf greenness or on the sum of chlorophyll. Nanti variety, having small seed, turns out to have the largest leaf area but is not shade tolerant. The large leaf area may be due to the forming of tetra foliate leaves on Nanti variety. The form of chloroplast of Anjasmoro variety in 70% shading is better than other varieties. Therefore, determining leaf status can identify shading tolerant of soybeans.